THE INFLUENCE OF BRAND IMAGE, ADVERTISING, PERCEIVED PRICE TOWARD CONSUMER PURCHASE INTENTION (CASE STUDY: SAMSUNG SMARTPHONE) - Manorek, Sutria Langling (Jurnal Berkala Ilmiah Efisiensi, 2016)
ABSTRACT Smartphone has been quite a phenomenon especially in Manado city when finding people own more than one is easy. There are so many company involves in Smartphone market one of them is Samsung a Korean company who has been selling many Smartphone despite of a raging battle of competitions, this has become a questions for many people. Marketing is needed for the process of buying and selling a product or service, marketing as a liaison to the process or it can be regarded as a market that meet the seller and the buyer in the transaction processing. In this study takes several variables; Brand, Advertising and Perceived Price as variables that influence consumer purchase intention for research conducted on Samsung Smartphone with 100 questionnaire distributed to the users of Samsung. The results show there was significant and the effect of Brand Image, Perceived Price and Advertising Toward Consumer Purchase Intention. Keywords: Brand, Advertising, Perceived Price.